MIMO channels: optimizing throughput and reducing outage by increasing multiplexing gain - Oboyerulu Agboje; Nsikan Nkordeh; Uzairue Stanley Idiake; Ololade Oladoyin; Kennedy Okokpujie; Ibinabo Bob-Manuel (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The two main aims of deploying multiple input multiple out (MIMO) are to achieve spatial diversity (improves channel reliability) and spatial multiplexing (increase data throughput). Achieving both in a given system is impossible for now, and a trade-off has to be reached as they may be conflicting objectives. The basic concept of multiplexing: divide (multiplex) transmit a data stream several branches and transmit via several (independent) channels. In this paper, we focused mainly on achieving spatial multiplexing by modeling the channel using the diagonal Bell Labs space time scheme (D-BLAST) and the vertical Bell Labs space time architecture (V-BLAST) Matlab simulations results were a lso given to further compare the advantages of spatial multiplexing.